Molecular detection of interleukin-1A +4845 G→T gene in aggresive periodontitis patients - Chiquita Prahasanti; Harianto Notopuro (Universitas Airlangga, 2012)
Background: Abundant researches had been conducted based on the clinical and histopathological pathogenesis of aggresive periodontitis. Nevertheless, there were still few researches which based on molecular biology, and especially related to gene polymorphism. This study was done based on IL-1A +4845G→T gene polymorphism in aggressive periodontitis patients. Purpose: The purpose of this tudy was to characterized the generic variation of IL-1A +4845G→T as a risk factor aggressive periodontitis and chronic periodontitis. Methods: DNA from patients with aggressive periodontitis and chronic periodontitis was taken determination of IL-1A +4845 G→T polimorphism was conducted with PCR-RFLP technique. Results: Homozygous allele TT polymorphism was not found in all samples, only allele GG (wild type) and allele GT (heterozygous mutant) were not affect aggressive periodontitis and chronic periodontitis. Conclusion: The study showed there was no significant association between IL-1A +4845G→T gene polymorphism and aggressive periodontitis and chronic periodontitis. <span style="font-family: Tribune-Italic; font-size: 9pt;